The development and evaluation of reference materials for Lassa virus molecular diagnostics - Bentley, Emma M.; Richardson, Samuel; Atkinson, Eleanor; Rigsby, Peter; Emperador, Devy M.; Killip, Marian; Page, Mark; Mattiuzzo, Giada (Frontiers in Virology, 2025)
IntroductionRecent public health emergencies of international concern (PHEIC) have highlighted the need to develop prophylactic treatments and effective diagnostics for pandemic preparedness. In particular, the 100 Days Mission, an initiative to respond to a PHEIC within the first 100 days after declaration, has put into focus the importance of the early availability of effective diagnostic tests. Reference materials are valuable to support the development, assessment and calibration of these tests. The use of World Health Organization (WHO) International Standards (IS), the highest order calibrant, allows for the harmonisation of data reporting which assists performance evaluation. WHO IS for emerging virus molecular testing are usually made by inactivating the pathogen of interest and they undergo extensive evaluation in multi-laboratory collaborative studies. However, the development of such reference material for Lassa virus (LASV) is challenging due to the requirement for high containment level facilities to handle LASV. Further, the development of molecular tests for the detection of LASV RNA is confounded by the high sequence diversity amongst circulating lineages and a need to evaluate performance against them.MethodsTo circumvent this, we have developed a low containment alternative using chimeric lentiviral particles packaging the RNA of five prototype LASV lineages. These were evaluated alongside the whole inactivated virus (Josiah strain) by 18 laboratories, across 25 methods, as part of an International multi-lab collaborative study.ResultsThe data showed equivalent performance to the authentic virus in reducing interlaboratory variability; also, they highlighted the variability in detection across LASV lineages and supported the establishment of the chimeric particles as a WHO Reference Panel for Lassa virus RNA, alongside a WHO IS. This will greatly facilitate molecular test development and evaluation.DiscussionOverall, the strategy has the flexibility to be applied to a range of high priority viral families and can rapidly be implemented to expand to new viral sequences of high consequence which may impact molecular test performance. This represents an important pandemic preparedness initiative to support the response to the next outbreak, including Disease X.